Does the Conclusion of a DTA Serve the Fiscal Interests of High Tax Jurisdictions? - Castelyn, Donovan (2020)
This article examines whether the fiscal interests of high tax jurisdictions, considered in the context of both developed and developing nations, are promoted or, in the alternative, preserved when concluding double tax agreements (DTAs) with low tax jurisdictions or those with territorial tax bases. To resolve this position, the article considers the main tax fiscal and political drivers which motivate a jurisdiction to conclude a DTA. These drivers will then be contrasted with the specific tax policy objectives of high tax jurisdictions which forms the contextual framework for analysis. The central thesis of this article is that, regardless of the constitution of the high tax jurisdiction, the conclusion of a DTA with low tax or territorial counterparts broadly achieves an outcome contrary to the fiscal interests and objectives of the high tax jurisdiction, and often at the significant expense of the tax base.